Association between serum carotenoids levels and severe headache or migraine in adults: a cross-sectional study from NHANES - Hu, Tian; Chen, Yufei; Chen, Siyu; Xue, Rui (Frontiers in Nutrition, 2025)
BackgroundCarotenoids are well-established for their potent antioxidant properties; however, their potential association with severe headaches or migraines remains largely unexamined. This study was conducted to explore the relationship between serum carotenoid levels and the prevalence of severe headaches or migraines within the US population.MethodsWe utilized data from the 2001–2004 National Health and Nutrition Examination Survey (NHANES), which comprised a total of 8,910 participants. Serum carotenoid levels—specifically α-carotene, β-carotene, β-cryptoxanthin, lutein/zeaxanthin, and lycopene—were quantified using high-performance liquid chromatography. Migraine status was determined based on a questionnaire. The research methodologies employed included multivariate logistic regression, subgroup analysis, and restricted cubic spline (RCS) models.ResultsThe prevalence of migraines in the study population was 22.37%. Multivariate logistic regression analysis indicated that serum concentrations of α-carotene (OR = 0.91, 95% CI: 0.85–0.97), β-carotene (OR = 0.88, 95% CI: 0.81–0.94), β-cryptoxanthin (OR = 0.83, 95% CI: 0.76–0.90), lutein/zeaxanthin (OR = 0.75, 95% CI: 0.67–0.85), and total carotenoids (OR = 0.79, 95% CI: 0.70–0.90) were significantly inversely correlated with severe headaches or migraines; however, no significant association was found for lycopene levels. RCS analysis showed that β-cryptoxanthin had an L-shaped non-linear relationship with migraine prevalence at a threshold of approximately 9.392 μg/dL, while subgroup analyses confirmed the consistent inverse association between total serum carotenoid concentrations and migraine prevalence across various groups.ConclusionSerum concentrations of α-carotene, β-carotene, β-cryptoxanthin, lutein/zeaxanthin, and total serum carotenoids were inversely correlated with the incidence of severe headaches or migraines in US adults. This evidence indicates that carotenoids may provide a protective effect against migraines; however, further investigation is warranted to substantiate these associations and to elucidate the underlying mechanisms.